Successful endotracheal intubation with Trachway after failed fiber-optic manipulations in a patient with retropharyngeal cervical chordoma - Yi-Ting Chen; Chun-Ning Ho; Kuo-Chuan Hung (Tzu-Chi Medical Journal, 2017)
A retropharyngeal mass may distort the airway anatomy and reduce the space available for manipulation of intubation devices. We encountered a patient with a cervical chordoma occupying the retropharyngeal space. Fiber-optic orotracheal intubation was attempted to secure the airway. Although the fiber-optic bronchoscope (FOB) was successfully placed into the trachea, the tracheal tube could not be passed through the glottis. An airway was then successfully established with the Trachway device, a video-assisted system with a rigid but malleable intubating stylet. In conclusion, although a FOB is commonly used to secure a difficult airway, the present case report demonstrates that fiber-optic intubation is not always successful. Video intubation devices with a rigid stylet (such as Trachway) may be helpful in patients with a cervical chordoma. We suggest this device be available as backup for patients with distorted airway anatomy.